ANALYSIS OF THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEE PERFORMANCE OF PT. WIJAYA KARYA (PERSERO) TBK. AT THE NAYUMI SAM TOWER MALANG PROJECT - Siagian, Ade Onny (LPPM STMIK Dharmapala Riau, 2020)
Human resources is one of the factors that affect production in a company, Because without human company could not go on, In fact it is now up to the present time the individual human being at main asset an enterprise in administered a set of production activities, This was because human beings have thought and your moral understanding, a feeling, energy, the level of knowledge, and creativity to accomplish a purpose a public social security agency. Maximum performance can be influenced by the work safety and health. This study attempts to know how big the influence of work safety and health on performance employees on PT. Wijaya Karya Nayumi Sam Tower Malang Project. The research was conducted between January 2018 and up to May 2018. Methods used is the quantitative method, technique data collection used is a study literature and spreading the questionnaire shown to an employee on PT. Wijaya Karya Nayumi Sam Tower Malang Project As many as 65 people. Sample selection in a non probability sampling techniques saturated sample. A method of analysis of data used was a validity test, reliability test, normality test, multiple linear regression, t test and f test and the coefficients of determined. The research results show that simultaneously variable work safety and health simultaneously influences employee performance at Nayumi Sam Tower Malang project As much as 50.4% while the rest is influenced by the other factors that not investigated in this study. Key Word: Safety, health and employee performance